Retelling Scripture : "the Jews" and the scriptural citations in John 1:19-12:15 - Sheridan, Ruth. (Biblical Interpretation Series, 2012)
The last century of scholarship on the Old Testament citations in the Gospel of John has concentrated almost exclusively upon source-critical or redaction-critical issues with the aim of determining the Christological import of the citations. The current book brings a narrative-rhetorical methodology to bear upon the seven explicit Scriptural citations in the Gospel's 'Book of Signs' (1:19-12:50) that are prefaced by a distinct introductory formula (1:19-12:15). These citations are each addressed to, or imply, a particular textual audience, namely, 'the Jews'. This book argues that as such the citations do not merely have Christological significance but function at the narrative level to encourage an ideal reader to construct a particularly negative characterization of 'the Jews'.